DEVELOPING SETS- BASED INQUIRY APPROACH STUDENTS WORKSHEET TO IMPROVE THE HIGH SCHOOL STUDENTS MATERIAL MASTERY AND SCIENTIFIC PROCESS SKILL ON WORK AND ENERGY MATERIAL - Fadilah Rohmah , Rahayu Dwisiwi S.R (Universitas negeri Yogyakarta, 2018)
Abstrak Penelitian ini bertujuan untuk menghasilkan LKPD pendekatan inkuiri berbasis SETS yang layak digunakan untuk pembelajaran, mengetahui peningkatan penguasaan materi menggunakan LKPD pendekatan inkuiri berbasis SETS, dan mengetahui pencapaian keterampilan proses sains menggunakan LKPD pendekatan inkuiri berbasis SETS. Penelitian ini merupakan penelitian pengembangan dengan model ADDIE. Subjek penelitian ini adalah siswa kelas X IPA 1 dan X IPA 2 SMA Ali Maksum. Hasil menunjukkan produk LKPD pendekatan inkuiri berbasis SETS layak digunakan untuk pembelajaran dengan tingkat persetujuan validator 91,91% , besar peningkatan penguasaan materi pada uji terbatas adalah 0,69 kategori sedang dan uji lapangan adalah 0,75 kategori tinggi. Pencapaian keterampilan proses sains uji terbatas pertemuan pertama 54,45 % kategori kurang baik, pertemuan kedua 78,48 % kategori baik, pertemuan ketiga 90,76 % kategori sangat baik. Pencapaian keterampilan proses sains uji lapangan pertemuan pertama 56,67 % kategori kurang baik, pertemuan kedua 71,42% kategori cukup, pertemuan ketiga 79,28% kategori baik. Kata kunci : LKPD, Pendekatan Inkuiri, SETS , Usaha dan Energi Abstract This study aimed at developing feasible SETS-based Inquiry approach students worksheet for the learning process, discovering the improvement of material mastery by using SETS-based inquiry approach student worksheet, and finding out the achievement of scientific process skill by using SETS-based inquiry approach student worksheet. This study was categorized as Research and Development with the ADDIE model. The subject of this study was the students of class X IPA 1 and X IPA 2 of SMA Ali Maksum. The result of the study showed that SETS-based inquiry approach student worksheet was feasible by the validators' approval 91.91%, the improvement of material mastery in preliminary testing was 0.69 and was categorized as medium and 0.75 for the main testing and was categorized as high. The achievement the scientific process skill in the first meeting was 54.45% and was categorized as very not good in the preliminary testing and 56.67% and was categorized as not good in the main testing, the second meeting, 78.48% and was categorized as good in preliminary testing and 71.42 and was categorized as good in main testing, the third meeting, 90.76% and was categorized as very good in preliminary testing and 79.28 and was categorized as good in the main testing. Keywords: Student Worksheet, Inquiry approach, SETS, Work and Energy